Molecular detection and identification of Ehrlichia and Anaplasma species in ixodid ticks - Aktas, Munir; Altay, Kursat; Dumanli, Nazir; Kalkan, Ahmet (Springer, 2009)
A polymerase chain reaction (PCR) assay followed by partial sequencing of the 16S ribosomal RNA gene was performed for the presence of Ehrlichia and/or Anaplasma. A total of 242 ixodid ticks were collected from domestic ruminants and their shelters, as well as humans, and their individual salivary glands were dissected out for DNA. From the 242 ticks analyzed, six (2.47%), comprising three Hyalomma anatolicum anatolicum, one Rhipicephalus bursa, and two Rhipicephalus sanguineus, were positive. Of these sequenced samples directly obtained from the PCR products, three sequences from H. a. anatolicum were identical to that of the gene of Ehrlichia spp. strains. One sequence identified in R. bursa was closely related to Anaplasma platys. The remaining two sequences detected in R. sanguineus were similar to that of the gene of Anaplasma ovis. The study presented here provides preliminary data regarding the presence of rickettsial pathogens in ticks in Turkey.
Keywords: Burgdorferi Sensu-Lato; Line Blot Hybridization; Fever Group Rickettsiae; Ovis; Dogs; Marginale; Platys; Phagocytophila; Ruminantium; Chaffeensis